PORTUGUESE RESISTANT HYPERTENSION POPULATION: IS IT POSSIBLE A RISK SCORE?. (April 2021) - Pereira, Flávio; Lopes, Susana; Briosa, Ana; Cavadas, Susana; Mesquita, José
Abstract: Objective: Introduction: Resistant hypertension isn't well studied with Ambulatory blood pressure monitoring (ABPM). Study in a RH population obtained in hypertension department to characterize it and identify cardiovascular (CV) outcome predictors. Design and method: ABPM - collected 1999–2018. Identified RH patients according to the ESC Guidelines 2018. Sample was characterized and analysed for predictors of CV events (CVe). CVe were ischaemic (IS), haemorrhagic stroke (HS), transient ischaemic attack (if hospitalized - TIA), acute coronary syndrome (ACS), acute heart failure (if hospitalized - AHF), peripheral arterial disease (PAD). Follow-up finished with event, the last evaluation of the patient or death. Statistical significance was assumed if p < 0.05. Results: Sample - 268 patients (161 males and 107 females) with RH. Age - 60.4 + /- 11.3 years (mean + /- SD). Follow-up - 5.5 + /- 4.9 years. Diabetes Mellitus (DM) - 44.4%, dyslipidaemia -75.4%, obesity - 45.1%, Chronic Kidney Disease (CKD) - 32.1%, history of previous CVe - 34.7% (PCVe). CVe observed - 55 (18 IS, 3 HS, 1 TIA, 16 ACS, 11 AHF, 6 PAD). 12 death from non-CVe. When the sample was analysed events vs no-event, those who with event, were older, had higher glycaemia, more prevalence of DM, history of PCVe and CKD. In Univariate Cox analysis for the prognosis of future CVe, it was significant: gender, DM, PCVe, age, glycaemia (Table 1). In a multivariate Cox Analysis with all these variables in the same sample, those who stood significant: glycaemia, age, gender, PCVe (Table 1). Even when these variables were adjusted to 24 h systolic blood pressure (24SBP) and night-time blood pressure (NSBP), they remained significant, but the 24SBP and NSBP didn't (Table 1). In Kaplan-Meier survival curve free of events, being male, history of PCVe revealed worst survival prognosis (respectively log rank 5.74, p < 0.05; 18.50, p = 0.000). Conclusions: In our population of RH, age, glycaemia, male, DM and history of PCVe are associated with markers of worst prognosis independent of blood pressure values. Perhaps in the future in larger samples, these variables can be taken in account for a risk score. Figure. No caption available.